Fine tunability of optical gain characteristics of InGaAs/GaAsSb/InAlAs nano-heterostructure under combined effect of field and temperature. (August 2021) - Khan, M. Imran; Hasan, P.M.Z.; Danish, Ekram Y.; Aslam, Mohammad; Kattayat, Sandhya; Kumar, Shalendra; Dalela, Saurabh; Ahmad, M. Ayaz; Alvi, P.A.
Abstract: The high optical gain of InGaAs/GaAsSb/InAlAs nano-scale heterostructure has motivated us for its further study under variable temperature and electric field. The presented work is devoted to show the impact of variable temperature and electric field on optical gain characteristics of InGaAs/GaAsSb/InAlAs nano-scale heterostructure which has been assumed to grow on lattice matched GaAs substrate. A six band k.p approach has been utilized to optimize the heterostructure in terms of carrier's wavefunctions, local carriers' density in conduction and valence band and dispersion curves followed by calculating momentum matrix elements and the optical gain spectra. According to the calculation results, the increasing range of temperature (having range of 100–300 K at the interval of 50 K) can control the peak gain significantly (6070 cm −1 to 4470 cm −1 ) with the red shift in wavelength; while enhanced order of electric field at room temperature can control the gain slightly (4470 cm −1 to 4150 cm −1 ) with fine red shift in wavelength. The results achieved in this work will definitely prove the method of controlling the gain characteristics as excellent; and the heterostructure studied will be suitable in design of tunable NIR (near infrared) light sources. Highlights: Design of novel QW heterostructure having W-shape structure with type-II nature. Suitable heterostructure for high peak optical gain. Broad tuning of gain characteristics with red shifted wavelength on temperature increase. Fine tuning of the gain characteristics by increasing the field strength with red shifted wavelength. Suitable for operation with fine tuning between the wavelength region 1550–1680 nm.